Raw Seismic Shot Time Navigation Data acquired during the Robert D. Conrad expedition RC2113 (1978) ... - Buhl, Peter; Stoffa, Paul; Talwani, Manik (Interdisciplinary Earth Data Alliance (IEDA), 2006)
This data set was acquired with a LDEO Multi-Channel Seismic system during Robert D. Conrad expedition RC2113 conducted in 1978 (Chief Scientist: Dr. Robert Leyden; Investigator(s): Dr. Peter Buhl, Dr. Paul Stoffa, and Dr. Manik Talwani). These data files are of Text File (ASCII) format and include Seismic Shot Time Navigation data that have not been processed. Data were acquired as part of the project(s): Norwegian Sea - The Application of Multichannel Seismic Reflection/Refraction techniques to measure velocity and thickness, to help establish the transition from oceanic to continental crust, to add information to what is known about the voring plateau and escarpment, the Faroe-Shetland escarpment, the Lofoton basin and trends in basement gravity highs along the shelf edge., and funding was provided by NSF grant: 439-5061-5973. ...